Paper-based hydrogen peroxide sensors using porphyrin with central ions of Ti - Lee, Dong-Jin; Byun, Young Tae; Kim, Sun Ho (2018 12TH INTERNATIONAL CONFERENCE ON SENSING TECHNOLOGY (ICST), 2018)
We demonstrate the paper-based hydrogen peroxide sensors for the biomedical and healthcare applications. Porphyrin with central ions of Ti is coated on a PDMS/paper substrate, and Au interdigitated electrodes are sputtered on the porphyrin/PDMS/paper substrate for the sensor applications. The fabricated sensors show a good response in the range of ca. 2 similar to 90 ppm of hydrogen peroxide vapor, and high selectivity to NH3, H2S, CO, and NO gases, which are representative biomarkers including exhaled breath.